Gambaran Penerimaan Diri (Self-Acceptance) pada Orang yang Mengalami Skizofrenia - Witrin Gamayanti (Psympathic : Jurnal Ilmiah Psikologi, 2016)
In general, people with schizophrenia have damaged reality testing which make them disconnected from their social environment. Despite being entered in the residual phase, it is still reluctant to interact with other people and have not productive yet in utilizing his/her capabilities. But the researchers also saw some people with residual schizophrenic who able to be productive as well as socialization; it associated with their acceptance to his/her self and its disorders. This study intended to figure out the image of self-acceptance of people with residual schizophrenia while they suffered with a large of pressures. This study used a qualitative method with case study design. The subjects of research were the people with residual schizophrenia with age range of 20 to 40 years old. From the research, it was found that the people with residual schizophrenia that can be productive and actively involved in social environment effected by the acceptance of him/herself although the self-acceptance quality was different among subjects